EFFECT OF STEVIA REBAUDIANA ON MORPHO-FUNCTIONAL INDICATORS OF PERIPHERAL BLOOD (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
Rich in natural antioxidants, Stevia rebaudiana has immunoregulatory, anti-stress, anti-inflammatory, antiviral, antihistaminic properties, increases the body's nonspecific defense, bioenergetic level, and improves tissue respiration. We have studied the long-term effect of S. rebaudiana on morphofunctional parameters of peripheral blood.
Keywords: $Stevia$ $rebaudiana$; erythrocytes; reticulocytes; leukocytes; differential white blood cell count